Teaching Reading Narrative Texts through Inking Your Thinking Strategy - masagus sulaiman; Siti Hadiyati Rohmana; Indawan Syahri (ELT-Lectura, 2019)
Abstract: The facts and phenomenon that most of senior high school students still encounter or face problems in understanding and answering the questions in reading texts led the researchers to conduct this quasi-experimental research, in line with teaching reading narrative through Inking Your Thinking strategy. This research is aimed at figuring out whether or not there is any significant difference in the tenth grade students’ reading comprehension achievements at SMA Negeri 2 Prabumulih among those who are taught by using Inking Your Thinking strategy and those who are not. To collect the data and to meet the objectives, the researchers used two kinds of tests (i.e. pretest and posttest) which were given to 62 students. To analyze the data, the researchers used T-test. The results of the difference analyses on experimental and control groups by using independent sample t-test showed that t-obtained was 4.839 greater than t-table which was 1.671 at the significant level p<0.05 in two tailed testing with df=60. It means that there was significant difference in students’ reading comprehension achievements among those who are taught by using Inking Your Thinking strategy and those who are not. In conclusion, Inking Your Thinking strategy can improve students’ reading comprehension achievements. Keywords: inking your thinking strategy, reading comprehension, narrative text